2013
DOI: 10.3996/042010-jfwm-009
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Rearing Densities to Improve Growth and Survival of Hatchery Spring Chinook Salmon

Abstract: We evaluated growth and survival of spring Chinook salmon Oncorhynchus tshawytscha reared at varying densities at Warm Springs National Fish Hatchery, Oregon. For three consecutive brood years, density treatments consisted of low, medium, and high groups in 57.8-m3 raceways with approximately 16,000, 24,000, and 32,000 fish/raceway, respectively. Fish were volitionally released in both the autumn and spring to mimic the downstream migration timing of the endemic wild spring Chinook salmon stock. Just prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The rearing densities maintained at the CESRF were generally at the lower end of the range reported by Chinook Salmon rearing studies (Ewing and Ewing 1995). Reduced rearing densities may confer behavioral and survival advantages to hatcheryorigin fish (Brockmark and Johnsson 2010;Olson and Paiya 2013). We also used factorial mating at the CESRF, which can increase effective population size (DuPont-Nivet et al 2006; and thus conserve genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The rearing densities maintained at the CESRF were generally at the lower end of the range reported by Chinook Salmon rearing studies (Ewing and Ewing 1995). Reduced rearing densities may confer behavioral and survival advantages to hatcheryorigin fish (Brockmark and Johnsson 2010;Olson and Paiya 2013). We also used factorial mating at the CESRF, which can increase effective population size (DuPont-Nivet et al 2006; and thus conserve genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Banks and LaMotte [39] found that rearing density had a minor, inconsistent effect on smolt to adult survival. Olsen and Paiya [40] reported mixed effects of lower density on adult survival; however they thought their low, medium and high experimental densities would all be considered to be low rearing densities. They, and [41], suggested that lower rearing densities enhanced survival when ocean conditions were poor.…”
Section: Discussionmentioning
confidence: 99%
“…The weight and length were recorded for five individuals from each chamber before inoculation to determine experimental biomass. The densities for each tank were consistent with Soderberg et al (2013) and Olson and Paiya (2013). Density was treated as a whole plot treatment.…”
Section: Experimental Treatmentsmentioning
confidence: 99%